An Ecopsychological Perspective on Sustainability: The BlindSpot - Pye, Lori (European Journal of Sustainable Development, 2014)
As the 2015 deadline for the United Nation’s Millennium Development Goals (MDGs) approaches many of the goals and objectives for education, the development agenda and sustainability have not and will not be met.This suggests something is not working – there is a blind spot.The inability to achieve sustainability is based upon much deeper human narratives and behaviors that drive destructive practices: gender exclusion and violence toward women areamong these two core drivers. An ecopsychological education aims to exposeandtransform deeply rooted unconscious narratives that underlie human practices, policies, and decisionsabout how we respond toour world in both creative and destructive ways. Key words: ecopsychology, pedagogy, sustainability, gender, sustainable development, ecology, psychology, narrative